Sim for Life: Foundations—A Simulation Educator Training Course to Improve Debriefing Quality in a Low Resource Setting - Robinson, Traci; Santorino, Data; Dube, Mirette; Twine, Margaret; Najjuma, Josephine N.; Cherop, Moses; Kyakwera, Catherine; Brenner, Jennifer; Singhal, Nalini; Bajunirwe, Francis; Wishar, Ian; Lin, Yiqun; et al. (Simulation in Healthcare, 2020)
Introduction: Despite the importance of debriefing, little is known about the effectiveness of training programs designed to teach debriefing skills. In this study, we evaluated the effectiveness of a faculty development program for new simulation educators at Mbarara University of Science and Technology in Uganda, Africa. Methods: Healthcare professionals were recruited to attend a 2-day simulation educator faculty development course (Sim for Life: Foundations), covering principles of scenario design, scenario execution, prebriefing, and debriefing. Debriefing strategies were contextualized to local culture and focused on debriefing structure, conversational strategies, and learner centeredness. A debriefing worksheet was used to support debriefing practice. Trained simulation educators taught simulation sessions for 12 months. Debriefings were videotaped before and after initial training and before and after 1-day refresher training at 12 months. The quality of debriefing was measured at each time point using the Objective Structured Assessment of Debriefing (OSAD) tool by trained, calibrated, and blinded raters. Results: A total of 13 participants were recruited to the study. The mean (95% confidence interval) OSAD scores pretraining, posttraining, and at 12 months before and after refresher were 18.2 (14.3–22.1), 26.7 (22.8–30.6), 25.5 (21.2–29.9), and 27.0 (22.4–31.6), respectively. There was a significant improvement from pretraining to posttraining (P<0.001), with no significant decay from posttraining to 12 months (P = 0.54). There was no significant difference in OSAD scores pre– versus post–refresher training at 12 months (P = 0.49). Conclusions: The Sim for Life Foundations program significantly improves debriefing skills with retention of debriefing skills at 12 months.
Keywords: Debriefing; Simulation; Faculty development; Training; Feedback